Characterizing the role of endocarp a and b cells layers during pod (silique) development in Brassicaceae - Justin B. Nichol; Marcus A. Samuel (Plant Signaling & Behavior)
The process of silique dehiscence is essential for the proper dispersal of seeds at the end of a dehiscent fruit plants lifecycle. Current research focuses on genetic manipulation to mitigate this process and enhance shatter tolerance in crop plants, which has significant economic implications. In this study, we have conducted a time-course analysis of cell patterning and development in valve tissues of Arabidopsis thaliana and closely related Triangle of U species (Brassica juncea, Brassica carinata, Brassica napus, Brassica rapa, and Brassica nigra) from Brassicaceae. The goal was to decipher the detailed temporal developmental patterns of the endocarp a and b cell layers of the valve, specifically their degradation and lignification respectively. Additionally, we propose a new classification system for the lignification of the endocarp a cell layer: L1 indicates the cell closest to the replum, with L2 and L3 representing the second and third cells, respectively, each numerical increment indicating lignified cells farther from the replum. Our findings provide a foundational framework absent in current literature, serving as an effective blueprint for future genomic work aimed at modifying valve structures to enhance agronomic traits, such as reducing fiber (lignin) or increasing shatter tolerance.